THE SOCIAL DETERMINANTS OF VACCINE HESITANCY: A REVIEW OF GLOBAL EVIDENCE - Weronika Skoczek; Julia Janecka; Michał Hofman; Jan Krzysztof Górski; Witold Romuald Gajewski (International Journal of Innovative Technologies in Social Science, 2025)
This review examines the social determinants that influence vaccine hesitancy and immunization rates globally. Key factors, including income, education, ethnicity, place of residence, and access to healthcare, are examined to highlight ongoing disparities in vaccine uptake. Vaccine reluctance remains most common among marginalized racial and ethnic groups, low-income communities, migrants, and individuals with limited education. However, recent data reveal a concerning rise in hesitancy among affluent and White populations in high-income countries. Additional influences, such as mistrust in health authorities, insufficient culturally sensitive care, and religious beliefs, further exacerbate these challenges. Evidence suggests that targeted interventions, including community-specific outreach, improved access to information, and engagement of trusted local leaders, can effectively reduce hesitancy. The review emphasizes the importance of developing equitable immunization strategies that address the unique social, cultural, and economic contexts of diverse groups. Addressing the root causes of vaccine hesitancy is crucial for rebuilding trust, narrowing health disparities, and advancing global vaccination goals.